極域熱圏の電磁エネルギー散逸と風速ダイナミクス - 大山, 伸一郎; 津田, 卓雄; 栗原, 純一; 藤井, 良一; 前田, 佐和子; 野澤, 悟徳; Shin-ichiro, Oyama; Takuo, T. Tsuda; Junichi, Kurihara; Ryoichi, Fujii; Sawako, Maeda; Satonori, Nozawa (2010)
第34回極域宙空圏シンポジウム 12月2日（木） 国立極地研究所 2階大会議室 conference object